Comparison of Antistreptolysin O Latex Screening Test with the Antistreptolysin O Hemolytic Test - Klein, George C. (Appl Microbiol, 1970)
This report describes a comparison of the Behringwerke antistreptolysin O (ASO) latex screening test with the ASO hemolytic test. Agreement between the two tests was poor when Difco streptolysin O (SLO) reagent was employed in the hemolytic test; approximately 34% of the sera with ASO titers in the normal range of the hemolytic test gave false-positive latex test reactions. However, the percentage of false-positive latex test reactions was only 5% when Behringwerke SLO reagent was used in the hemolytic test. An assay of the Difco and Behringwerke SLO reagents against an ASO standard indicated that the Difco SLO reagent was more potent than the Behringwerke SLO reagent. The lack of agreement between the Behringwerke latex test and the hemolytic test using Difco SLO reagent is attributed to the potency of the SLO reagents.